2021
DOI: 10.2147/bctt.s284453
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Influences in Breast Cancer Drug Resistance

Abstract: Breast cancer is the most common cancer in adult women aged 20 to 50 years. The therapeutic regimens that are commonly recommended to treat breast cancer are human epidermal growth factor receptor 2 (HER2) targeted therapy, endocrine therapy, and systemic chemotherapy. The selection of pharmacotherapy is based on the characteristics of the tumor and its hormone receptor status, specifically, the presence of HER2, progesterone receptors, and estrogen receptors. Breast cancer pharmacotherapy often gives differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 187 publications
(192 reference statements)
0
8
0
Order By: Relevance
“…The effectiveness of BC therapy using different modes of treatment with several anti-cancer drugs including classical chemotherapy, hormone, and targeted therapy tools has been extensively studied and discussed in the last decade [ 28 ]. However, despite the considerable progress that has been made in hormone-responsive breast cancer treatment, multi-drug resistance is a serious clinical problem, underlining the need for further advances [ 29 ]. Therefore, new therapeutic solutions are being sought that are effective in the treatment of breast tumors that are not susceptible to conventional treatment regimens.…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of BC therapy using different modes of treatment with several anti-cancer drugs including classical chemotherapy, hormone, and targeted therapy tools has been extensively studied and discussed in the last decade [ 28 ]. However, despite the considerable progress that has been made in hormone-responsive breast cancer treatment, multi-drug resistance is a serious clinical problem, underlining the need for further advances [ 29 ]. Therefore, new therapeutic solutions are being sought that are effective in the treatment of breast tumors that are not susceptible to conventional treatment regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Among these BC subtypes, TNBC is associated with poor survival mediated by treatment resistance, and it is the most difficult to treat with curative intent (Liao et al, 2021). Several drugs (e.g., anthracyclines and trastuzumab) have been approved by the U.S. Food and Drug Administration (FDA) for the treatment of BC; however, issues such as poor efficacy, toxicity, adverse drug reactions, and the emergence of drug resistance have limited their clinical use (Brower, 2013;Cameron et al, 2017;Shah and Gradishar, 2018;Daniyal et al, 2021;. Therefore, there is an urgent need to discover and develop new drugs for the treatment of BC, particularly for TNBC.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have shown that mutations in oncogenes and tumor suppressors such as K-Ras and P53 play an important role in the drug resistance of cancer cells. These mutations can cause significant changes in associated cellular signaling pathways leading to attenuated apoptosis, enhanced expression of ABC family transporter, and enhanced DNA repair [100][101][102][103][104]. In addition, many important receptors involved in cell growth and proliferation, various components of the signaling pathways associated with them, and a large number of proteins involved in proliferation and apoptosis may undergo mutations leading to enhanced proliferation and drug resistance.…”
Section: Crispr/cas9 Gene Editing Applications In Overcoming Drug Res...mentioning
confidence: 99%